Changes in saliva proteins in cows with mastitis: A proteomic approach. (November 2021) - Franco-Martínez, L.; Muñoz-Prieto, A.; Contreras-Aguilar, M.D.; Želvytė, R.; Monkevičienė, I.; Horvatić, A.; Kuleš, J.; Mrljak, V.; Cerón, J.J.; Escribano, D.
Abstract: This study aimed to evaluate the possible saliva proteome changes in cows with mastitis using a Tandem Mass Tags (TMT) proteomics approach. For this purpose, the salivary proteomes from healthy cows and cows with mastitis were analysed, and their serum proteomes were also studied for comparative purposes. A total of eight saliva and serum paired samples for each group were used for the proteomic study, and eight additional samples for each group were analysed in the analytical and overlap performance studies. In saliva samples, 2192 proteins were identified, being sixty-three differentially modulated in mastitis. In serum, 1299 proteins were identified, being twenty-nine differentially modulated in mastitis. Gamma glutamyl transferase ( γGT ) in saliva and serum amyloid A (SAA) were validated by commercially available automated assays. In conclusion, there are changes in protein expression and metabolic pathways in saliva and serum proteomes of cows with mastitis, showing different response patterns but complementary information. Highlights: TMT analysis show different response patterns in saliva and serum but complementary information. TMT analysis allowed the identification of original mastitis proteins in cow saliva. Salivary gamma glutamyl transferase could be a biomarker of mastitis in cows.